FEATURES OF MANIFESTATION OF SOCIAL TENSION IN INDUSTRIAL ORGANIZATIONS DURING THE PERIOD OF SOCIAL TRANSITIVITY - Olga F. Korol (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The relevance of the study is due to the prospect of application of its results in the field of predicting human social behavior. In this regard, the article is aimed at identifying the features of manifestation of social tension in organizations. The article reveals the content of the phenomenon of "social tension" in organizations. The author identifies the criteria for the analysis of the types of social tension in organizations: a) at the meso-level (the level of analysis of the organization as a whole and the level of interaction between personnel and organization); b) at the micro level (individual-personal level of analysis). The article presents and substantiates the criteria for the classification of types of social tension in the organization at each of the levels of analysis. The author reveals the content of each of the types of social tension at industrial enterprises. The main groups of types of social tension are identified. The materials of the article are of practical value for top managers of organizations and practicing psychologists for consultative, diagnostic and corrective activity aimed at reducing the level of social tension.